2021
DOI: 10.1111/1758-2229.12985
|View full text |Cite
|
Sign up to set email alerts
|

Novel Chlamydiae and Amoebophilus endosymbionts are prevalent in wild isolates of the model social amoeba Dictyostelium discoideum

Abstract: Amoebae interact with bacteria in multifaceted ways. Amoeba predation can serve as a selective pressure for the development of bacterial virulence traits. Bacteria may also adapt to life inside amoebae, resulting in symbiotic relationships. Indeed, particular lineages of obligate bacterial endosymbionts have been found in different amoebae. Here, we screened an extensive collection of Dictyostelium discoideum wild isolates for the presence of these bacterial symbionts using endosymbiont specific PCR primers. W… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 70 publications
0
7
0
Order By: Relevance
“…While not a direct demonstration of any fitness benefits, P. agricolaris and P. hayleyella show positive chemotaxis toward D. discoideum supernatant ( 17 ). Later, D. discoideum was discovered to also associate with unculturable Chlamydiae and Amoebophilus symbionts but with no obvious fitness effects of infection or clear patterns of coinfection with Paraburkholderia ( 18 ).…”
Section: Introductionmentioning
confidence: 99%
“…While not a direct demonstration of any fitness benefits, P. agricolaris and P. hayleyella show positive chemotaxis toward D. discoideum supernatant ( 17 ). Later, D. discoideum was discovered to also associate with unculturable Chlamydiae and Amoebophilus symbionts but with no obvious fitness effects of infection or clear patterns of coinfection with Paraburkholderia ( 18 ).…”
Section: Introductionmentioning
confidence: 99%
“…Like Paraburkholderia, we found that Chlamydiae is highly prevalent in natural populations, though the reasons for this are less clear. Laboratory studies of Chlamydiae in D. discoideum found no fitness cost of infection (Haselkorn et al, 2021), but potential benefits have yet to be explored. Like Paraburkholderia, Chlamydiae was overabundant in the microbiota that it occupied, resulting in compositional uniformity.…”
Section: Discussionmentioning
confidence: 99%
“…We re-sampled natural D. discoideum populations in the Virginia Mountain Lake area (Haselkorn et al, 2019(Haselkorn et al, , 2021. Soil, sampled from below the leaf litter layer of the forest floor or below rotting logs, was collected from ten different sites at each of four separate locations (Supplemental Table 1) and was plated on hay agar within 96 hours (Supplemental Table 2).…”
Section: Soil Collection and Amoeba Culturingmentioning
confidence: 99%
See 2 more Smart Citations